2011
DOI: 10.1097/fjc.0b013e31820270bb
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Treatment Inhibits Vascular Endothelial Senescence and Asymmetrical Dimethylarginine in Ovariectomized Rabbits

Abstract: To investigate the effects of estrogen treatment on aortic endothelial senescence and atherosclerosis, an ovariectomized female rabbit model was constructed, and human umbilical vein endothelial cells were utilized to explore the potential mechanisms. Twenty-eight female rabbits were randomized into 4 groups (7 each): sham operation, ovariectomized, ovariectomized plus low-dose estradiol treatment, and ovariectomized plus high-dose estradiol treatment. All rabbits were fed on high-cholesterol diet for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…43,44 Hormone therapy in postmenopausal women (or OVX animal) could limit the uptake of cholesterol ester into the arterial wall, reduce oxidative stress, improve NO-mediated endothelium-dependent vasodilation and exert cardiovascular protection. 6,45,46 In the present study, ovariectomy plus HFD reduced the vasorelaxation induced by ACh (endothelium-dependent relaxation) without affecting that induced by SNP (endothelium-independent relaxation), suggesting LCEE could protect the endothelium from the detrimental effect of ovariectomy plus HFD. It was found that there was a partial loss of endothelial function in the aorta from the Control group rats since the maximum relaxation with ACh is around 60% of the contraction induced by phenylephrine (1 mM) (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…43,44 Hormone therapy in postmenopausal women (or OVX animal) could limit the uptake of cholesterol ester into the arterial wall, reduce oxidative stress, improve NO-mediated endothelium-dependent vasodilation and exert cardiovascular protection. 6,45,46 In the present study, ovariectomy plus HFD reduced the vasorelaxation induced by ACh (endothelium-dependent relaxation) without affecting that induced by SNP (endothelium-independent relaxation), suggesting LCEE could protect the endothelium from the detrimental effect of ovariectomy plus HFD. It was found that there was a partial loss of endothelial function in the aorta from the Control group rats since the maximum relaxation with ACh is around 60% of the contraction induced by phenylephrine (1 mM) (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…17 β ‐Estradiol also upregulates the expression of SIRT1; this effect may contribute to the reduced senescence development and endothelial dysfunction in blood vessels of ovariectomized animals with 17 β ‐estradiol administration (Liao et al . , Bendale et al . ).…”
Section: Gender Differences In Edhmentioning
confidence: 99%
“…Estrogens improve glucose tolerance and responsiveness to insulin in part through direct effects on insulin receptor levels in adipocytes in rat [25]. Feeding mice with estradiols reduced the levels of total cholesterol, and low-density lipoprotein (LDL) cholesterol [26].…”
Section: Effects Of Estrogen and Folic Acid On Body Weight And Blood ...mentioning
confidence: 99%